The clinical efficacy of biportal endoscopy is comparable to that of uniportal endoscopy via the interlaminar approach for the treatment of L5/S1 lumbar disc herniation - Zuo, Rujun; Jiang, Yi; Ma, Ming; Yuan, Shuai; Li, Jian; Liu, Chang; Zhang, Jiexun (Frontiers in Surgery, 2022)
Objective: To compare the clinical outcomes of unilateral biportal endoscopy/biportal endoscopic spinal surgery (UBE/BESS) via the posterior approach with those of interlaminar endoscopic lumbar discectomy (IELD) for the treatment of L5/S1 lumbar disc herniation. Results: One case incurred dural tear in the UBE/BESS group, and one case developed recurrence in the IELD group. Postoperatively, the VAS score and ODI index decreased significantly in both groups (P< 0.01). VAS and ODI scores (preoperative as well as 3 days, 3 months, 6 months, and 12 months after surgery), the overall operative time, and postoperative hospital stay were not significantly different between the two groups (P>0.05). No statistical difference in intraoperative radiation exposure dose was noted between the two groups (P> 0.05). The surgical incision length was greater in the UBE/BESS group (P<0.01), and pre- and postoperative hemoglobin changes were more pronounced in the UBE/BESS group (P<0.01). The UBE/BESS group had a longer extracanal operative time and shorter intracanal decompression time (P<0.01). Conclusions: The clinical efficacy of UBE/BESS for L5/S1 lumbar disc herniation is comparable to that of IELD. Intraoperative radiation exposure doses were similar in both techniques. UBE/BESS required more time to identify tissue structures and a larger working space when operating outside the spinal canal; however, the efficiency of nucleus pulposus removal and nerve root release inside the spinal canal superseded that in IELD. Furthermore, the surgical incision in the UBE/BESS technique was longer, with greater actual blood loss during surgery, thus rendering UBE/BESS inferior to the IELD technique in terms of surgical trauma. Nonetheless, no significant difference was noted between the two techniques in the postoperative recovery time of patients.